2011
DOI: 10.1007/s10562-011-0741-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nanostructured SilicaCat Pd0

Abstract: Structural investigation on nanostructured\ud SiliaCat Pd0 palladium catalyst sheds light into the origins of the remarkable activity of these new catalytic materials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Sol−gel encapsulation within the organosilica cages, in its turn, ensures high chemical and physical stabilization of the entrapped nanoparticles. 8 Another advantageous feature of this new catalyst is that it does not require the typical deaerated conditions typical of Sonogashira coupling reactions using palladium(0) complexes, which are unstable in the air. We now show how to broaden the scope of the method under thermal conditions to couple different iodo-and bromoarenes with phenylacetylene, accessing enhanced reaction rates and conversions via microwave irradiation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Sol−gel encapsulation within the organosilica cages, in its turn, ensures high chemical and physical stabilization of the entrapped nanoparticles. 8 Another advantageous feature of this new catalyst is that it does not require the typical deaerated conditions typical of Sonogashira coupling reactions using palladium(0) complexes, which are unstable in the air. We now show how to broaden the scope of the method under thermal conditions to couple different iodo-and bromoarenes with phenylacetylene, accessing enhanced reaction rates and conversions via microwave irradiation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The presence of highly dispersed palladium NPs (ca. 2-4 nm) entrapped within the inner porosity of the lipophilic organosilica matrix [25] was clearly revealed by TEM analysis before and after scale-up catalyst synthesis ( Table 1, Figures 2a and 2b). The crystallinen ature of the active nanophase is evident from the XRD pattern of the catalyst powder ( Figure 3), characteristic of the fcc structure of metallicPd.…”
Section: Resultsmentioning
confidence: 90%
“…Accordingly, previous preliminary investigation of the Silia Cat Pd 0 structure by solid state NMR [ 25 ] has shown that the degree of cross-linking does not correlate with the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%